2000
DOI: 10.1002/tl.849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Students' Written Performance in the Online Classroom

Abstract: Professors can evaluate students' written performance in the online classroom by using rubrics to assess content, expression, and participation. The e‐folio provides professors with a summative assessment in the online course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…The quality of each written report was evaluated by one of the authors and a senior research assistant who was blind to the study hypotheses. The coding scheme was developed from Bauer and Anderson (2000) and focused on four quality components: report expectations, content assessment, integration of optional source information, and expression in writing. 1 All components were rated on a 4-point Likert-type scale, and the overall quality of the report was calculated by averaging these four ratings.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of each written report was evaluated by one of the authors and a senior research assistant who was blind to the study hypotheses. The coding scheme was developed from Bauer and Anderson (2000) and focused on four quality components: report expectations, content assessment, integration of optional source information, and expression in writing. 1 All components were rated on a 4-point Likert-type scale, and the overall quality of the report was calculated by averaging these four ratings.…”
Section: Methodsmentioning
confidence: 99%
“…While little research has been found that analyzes the success of online high schools, much has been written regarding what experts believe should be taken into account when creating online courses. Consistent themes are that the courses ought to make use of a variety of technological techniques, be interactive, and emphasize student-to-student and student-to-teacher communication (Bauer & Anderson, 2000;Lopez, 2003). Student-centered, constructivist, online courses are often recommended where the instructor frames the discussions to be handled through student-to-student and/or student-to-teacher communication.…”
Section: Online High Schoolsmentioning
confidence: 99%
“…Others have proposed even more procedurally focused criteria, such as Bauer and Anderson (2000), who advocated assessment that focuses on the degree to which a student uses complex, grammatically correct sentences on a regular basis. Morrison and Ross (1998) recommended that points be deducted for off-topic comments students make to the collaborative discourse.…”
mentioning
confidence: 99%